Shifting baseline syndrome highlighted by anecdotal accounts from snapper (Ocyurus chrysurus) fishery - Zapelini, Cleverson; Sousa da Silva, Patricia; Schiavetti, Alexandre (Ethnobiology and Conservation, 2020)
The fishes of the Lutjanidae family are widely distributed throughout the Atlantic, Indian and Pacific Oceans and have relevant commercial importance. Yellowtail snapper (Ocyurus chrysurus) is a targeted species in the small-scale fishery of the northeastern coast of Brazil, notably for hand-line fishing. We used the local ecological knowledge (LEK) of three generations of fishers from Ilhéus (southern Bahia State, Brazil) to evaluate the perception of weight, best day of capture and relative abundance of the species. More experienced fishers captured the largest specimens, had larger catches and were more likely to indicate a decrease in species abundance. On the other hand, younger fishers had smaller catches and were more likely to indicate that the species abundance is stable or increasing. The results suggest the occurrence of shifting baseline syndrome among fishers and emphasize the importance of including information from fishers in the construction of management measures. Fishers can play a key role in developing viable proposals that are aimed at the management of fishing of species with spawning aggregation, such as yellowtail snapper.